1995
DOI: 10.1259/0007-1285-68-808-394
|View full text |Cite
|
Sign up to set email alerts
|

A method for estimating compressed breast thickness during mammography

Abstract: Measurements of compressed breast thickness during mammography is necessary for the calculation of breast dose. In theory, it should be possible to calculate breast thickness from the separation of images of radio-opaque markers attached to the compression paddle. Such a technique has been evaluated on two models of X-ray set using simulated and real breasts. The results show that breast thickness at a given position can be determined with an average error of about 2 mm by this method, which is likely to be ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 1 publication
0
14
0
1
Order By: Relevance
“…Compressed breast thickness was derived using a method similar to that of Burch and Law (1995). They proposed a thickness measurement based on the imaging of lead markers placed on the compression plate and by calibration of the breast thickness on the imaged positions of the lead markers.…”
Section: Methodsmentioning
confidence: 99%
“…Compressed breast thickness was derived using a method similar to that of Burch and Law (1995). They proposed a thickness measurement based on the imaging of lead markers placed on the compression plate and by calibration of the breast thickness on the imaged positions of the lead markers.…”
Section: Methodsmentioning
confidence: 99%
“…It is well known (Burch and Law 1995) that the indication of breast thickness on mammography units is not always reliable, since the compression plate can deform considerably. Burch and Law have proposed a thickness measurement based on the imaging of lead markers placed on the compression plate and by calibration of the breast thickness on the imaged positions of the lead markers.…”
Section: Determination Of Compressed Breast Thicknessmentioning
confidence: 99%
“…To adaptively quantify the amount of contrast material in breast, a priori knowledge of the breast thickness for each pixel is required. However, it is also known that the built-in thickness measurement is not accurate in many clinical mammography systems which employ a spring-loaded paddle [8,9]. Therefore, a triple-energy method is employed, which can provide a third image to overcome the limitation of the dual-energy method.…”
Section: Discussionmentioning
confidence: 99%
“…However, in many clinical mammography systems which employ a spring-loaded paddle, the physical thickness of the breast may not be uniform due to deformation and tilt of the compression paddle [7]. Furthermore, it is reported that the built-in thickness measurement is not accurate [8,9], which can affect the performance. Triple-energy CEDM, which provides a third image, has been considered to overcome the necessity of thickness information.…”
Section: Introductionmentioning
confidence: 99%